Kampanye dan Penggunaan Garam Beryodium di Desa Leuwiliang, Jawa Barat - Anggorodi, Rina (Kesmas, 2010)
Pada tahun 2002, sekitar 71,8% masyarakat Kabupaten Bogor mengonsumsi garam beryodium dengan kategori cukup yang jauh di bawah target Universal Salt Iodization (USI) > 90%. Penelitian dilakukan terhadap 39 informan para ibu bekerja dan tidak bekerja yang tinggal dan tidak tinggal dengan orang tua, petugas kesehatan, kader, ibu PKK, pedagang sembako yang ada di pasar dan warung di wilayah Kecamatan Leuwiliang. Informan yang tinggal dengan orang tua cenderung memilih garam curah karena orang tua menyukai garam tersebut. Sebaliknya, informan yang tinggal sendiri memilih garam beryodium tanpa dipengaruhi orang tua. Sementara, informan dengan tingkat pendidikan SMA dan D3 segera mengubah perilaku menggunakan garam beryodium. Ketersediaan garam dan daya beli masyarakat sudah baik. Peran kampanye garam beryodium bagi informan yang tinggal dengan orang tua cenderung memilih garam curah karena orang tua menyukai penggunaan garam tersebut. Sebaiknya informan yang tinggal sendiri memilih garam beryodium tanpa dipengaruhi orang tua. Pesan dalam kampanye mudah dimengerti, sehingga sampai kini masih diingat oleh para informan. Dalam penggunaan garam beryodium, informan tidak dipengaruhi umur dan pekerjaan, tetapi oleh pendidikan. Ketersediaan garam dan daya beli masyarakat sudah baik. In 2002, about 71.8% of community at District of Bogor consumed iodized salt at adequate category. This figure is far beyond the target of Universal Salt Iodization (USI), i.e.>90% of households consume high concentrate iodized salt. If the salt consumed fulfills the requirement it will minimize the problem of swollen goitre glands in the community. The study used qualitative method. Data were obtained through in-depth interview, focus group discussion, and iodized salt to test. There were 39 informers that consisted of mothers either having an occupation or not who lived or did not live with their parents, providers, cadres, family welfare and empowerment, sellers of daily living necessities in the market or stalls at Subdistrict of Leuwiliang. In general there was a difference between informers living with their parents and those living separately, either in those who worked or did not work. Informers living with their parents tended to choose salt in bricket because the parents liked it. Meanwhile informers living away from parents chose iodized salt without the influence of their parents. All informers said that the message was communicative and clearly delivered. There was no difference in behavioral changes based on age and occupation. There were informers with elementary or junior high school education found it difficult to change their behavior. Whereas informers with senior high school or diploma 3 education soon changed their behavior by consuming iodized salt after watching the campaign. Availability of salt and purchasing power of the community were relatively good. There was no special socialization about iodized salt conducted by providers. Informers living with their parents tended to choose salt in bricket because their parents liked it; on the other hand, informers living away from their parents preferred iodized salt without the influence of their parents. The message in the short campaign was memorable so that informers still remembered it. Behavioral changes of the informers in using iodized salt were not affected by age and occupation but by education. Availability of iodized salt and purchasing power of the community were relatively good.